The Translation Methods Used in the Subtitles of Dialogues in Maleficent Movie - Nurhandini, Andhita Hening; Wiyaka, Wiyaka; B, Th. Cicik Sophia (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The objectives of this research are to find out the translation methods used in the dialogues, to find out the method that often appears in the subtitles of Maleficent movies, and to describe the quality level of English to Indonesian subtitles in Maleficent's translation. The theory used to analyze the translation method is the theory of Gottlieb (1992). This research is classified into qualitative descriptive research. The research data is from dialogue subtitles in the Maleficent film. The data source is obtained from the film Maleficent—data collection techniques with documentation. At the same time, data analysis is done by collecting, classifying, calculating, dominating, and drawing conclusions. The results of this research indicate that translators use six methods. These methods are paraphrasing (16,1%) and transfer (39,5%). Imitation (8,0%), condensation (8,0%), decimation (0,6%), and deletion (27,8%). From these results, it can be concluded that the translation method that translators dominantly use is the transfer method. Besides, subsequent research can provide knowledge that can be useful for readers and can be the next related research that will be reviewed. Further research is also needed to keep up with the development of translation studies.